Extracellular vesicle-transmitted miR-671-5p alleviates lung inflammation and injury by regulating the AAK1/NF-κB axis - Lian, Jie; Zhu, Xinxing; Du, Jiang; Huang, Beijia; Zhao, Fengting; Ma, Chunya; Guo, Rui; Zhang, Yangxia; Ji, Longkai; Yahaya, Badrul Hisham; Lin, Juntang (Molecular therapy, 2023)
Mesenchymal stem cells regulate remote intercellular signaling communication via their secreted extracellular vesicles. Here, we report that menstrual blood-derived stem cells alleviate acute lung inflammation and injury via their extracellular vesicle-transmitted miR-671-5p. Disruption of this abundantly expressed miR-671-5p dramatically reduced the ameliorative effect of extracellular vesicles released by menstrual blood-derived stem cells on lipopolysaccharide (LPS)-induced pulmonary inflammatory injury. Mechanistically, miR-671-5p directly targets the kinase AAK1 for post-transcriptional degradation. AAK1 is found to positively regulate the activation of nuclear factor κB (NF-κB) signaling by controlling the stability of the inhibitory protein IκBα. This study identifies a potential molecular basis of how extracellular vesicles derived from mesenchymal stem cells improve pulmonary inflammatory injury and highlights the functional importance of the miR-671-5p/AAK1 axis in the progression of pulmonary inflammatory diseases. More importantly, this study provides a promising cell-based approach for the treatment of pulmonary inflammatory disorders through an extracellular vesicle-dependent pathway. [Display omitted] Menstrual blood-derived stem cells alleviate acute lung injury through extracellular vesicle-transmitted miR-671-5p, which directly targets AAK1 for degradation, and thus suppresses AAK1-mediated NF-κB signaling activation. These findings provide a promising cell-based approach for the treatment of pulmonary inflammatory injury.